2022
DOI: 10.3389/fenvs.2022.966479
|View full text |Cite
|
Sign up to set email alerts
|

Environmental protection and sustainable development of enterprises in China: The moderating role of media attention

Abstract: Faced with global environmental problems, such as global warming, enterprises have become important players in environmental protection. By fulfilling their environmental responsibilities, enterprises can create a good external image and gain support from the public and government, thereby increasing the influence of their enterprises. At the same time, the media plays the role of guiding public opinion and supervising the market economy in enterprise development and market economy. Therefore, this study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Specifically, both print and news media coverage positively moderate the effect of reactive GTI on CFP, which is consistent with Ren et al (2022) and Zhang et al (2022). Interestingly, new media coverage negatively affected the relationship between reactive and proactive GTIs and CFP, as supported by Liang et al (2022) and Wu et al (2022).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Specifically, both print and news media coverage positively moderate the effect of reactive GTI on CFP, which is consistent with Ren et al (2022) and Zhang et al (2022). Interestingly, new media coverage negatively affected the relationship between reactive and proactive GTIs and CFP, as supported by Liang et al (2022) and Wu et al (2022).…”
Section: Resultsmentioning
confidence: 72%
“…In line with the research methodology employed by Wu et al (2022), we used the Janis-Fadner (J-F) coefficient to gauge the moderating impact of media coverage derived from print and digital media data. Janis and Fadner (1965) introduced the J-F coefficient as a content analysis index.…”
Section: Moderating Variable-media Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Boscoianu et al [27] argue that innovation is the foundation of sustainable development for most companies. Wu et al [28] found that by bolstering innovation capabilities and shouldering social responsibilities, companies can notably enhance their sustainable development. Li et al [29] pointed out that increasing executive salaries would raise agency costs and diminish the potential for sustainable development within companies.…”
Section: Corporate Sustainable Developmentmentioning
confidence: 99%
“…The "livable path" is one in which the ecological footprint, i.e., the environmental burden, is kept low in line with future economic development and environmentally responsible companies tend to be more profitable (Wu et al, 2022). However, traditional economic approaches underestimate the risks from climate change and overestimate the costs of the low-carbon transition, as they do not consider the cumulative gains from path-dependent innovations (Ekins and Zenghelis, 2021).…”
Section: Literature Overviewmentioning
confidence: 99%